Analytical Simulation of Biocomposite Materials for Toyota Avanza Vehicle Cabin Lamp Light Covers Utilising Pandanus Tectorius Fibres with Epoxy Matrix as a Manufacturing Substitute to Cut Down on Plastic Waste - Faizin, Kholis Nur; Susanto, Fredy; Aziz, M. Shafwallah Al.; Amin, M. Chabib Nur (PT FORMOSA CENDEKIA GLOBAL, 2024)
Biocomposites, made from an epoxy matrix and pandan fibre, offer a biodegradable alternative to plastic. Fabricated through manual layer lay-up, the material underwent stress propagation analysis using SolidWorks simulation and automotive testing. Results indicate that failure occurs in pure tension when stress exceeds 60% of the flexural strength (1.2 MPa) due to longitudinal fibre rupture. With a Young's modulus of 2×10¹⁰ N/m², tensile strength of 13.6 MPa, and Poisson's ratio of 0.31, the material exhibited safe performance under loads nearly four times its capacity. The factor of safety, while as low as 0.5 in critical areas, confirms t